Hypocalcemic myopathy without tetany due to idiopathic hypoparathyroidism: case report - Daniel Bocchese Nora; Daniele Fricke; Jefferson Becker; Irineo Gomes (Arquivos de Neuro-Psiquiatria)
Myopathy due to idiopathic hypoparathyroidism is very unusual. We report on a 30 years-old man referred with complaints of sporadic muscle pain and mild global weakness for 10 years. His physical examination showed normal strength in distal muscle and slightly weakness in the pelvic and scapular girdles with no atrophy. Deep muscle reflexes were slightly hypoactive. Trousseau's and Chvostek's signs were absent. He had bilateral cataract and complex partial seizures. His laboratory tests showed decreased ionised and total calcium and parathyroid hormone and increased muscle enzymes. EMG and muscle biopsy was compatible with metabolic myopathy. After treatment with calcium and vitamin D supplementation he showed clinical, neurophisiological and laboratorial improvement. In conclusion: patients with muscle symptoms, even when non-specific and with normal neurological examination, should have serum calcium checked, as myopathy due to idiopathic hypoparathyroidism, even being rare, is treatable and easy to diagnose.